A Tray‐Shaped, PdII‐Clipped Au3 Complex as a Scaffold for the Modular Assembly of [3×n] Au Ion Clusters1. Issue 42 (28th August 2014) - Osuga, Takafumi; Murase, Takashi; Hoshino, Manabu; Fujita, Makoto
Abstract A tray‐shaped PdII3AuI3 complex (1) is prepared from 3, 5‐bis(3‐pyridyl)pyrazole by means of tricyclization with AuI followed by PdII clipping. Tray 1 is an efficient scaffold for the modular assembly of [3×n] AuI clusters. Treatment of 1 with the AuI3 tricyclic guest 2 in H2O/CH3CN (7:3) or H2O results in the selective formation of a [3×2] cluster (1⋅2) or a [3×3] cluster (1⋅2⋅1), respectively. Upon subsequent addition of AgI ions, these complexes are converted to an unprecedented Au3–Au3–Ag–Au3–Au3 metal ion cluster.